Preparedness of primary health care workers and audit of primary health centres for newborn resuscitation in Port Harcourt, Rivers State, Southern Nigeria - Briggs, Datonye Christopher (Pan Afr Med J, 2020)
INTRODUCTION: Nigeria still has high newborn deaths and birth asphyxia remains a major cause. Birth attendants´ readiness to perform newborn resuscitation depends largely on their competence in basic resuscitation and availability of newborn resuscitation equipment to enable the various steps outlined in resuscitation guidelines to be applied quickly and appropriately. This study aimed to assess primary health care workers´ experience of neonatal resuscitation and audit primary health centres for availability of neonatal resuscitation equipment. METHODS: this descriptive cross-sectional study surveyed 106 primary health care workers (22 doctors, 84 nurses) randomly selected from 28 Primary Health Centres to document their experiences in newborn resuscitation and appraise the centres for availability of newborn resuscitation equipment. Experience in newborn resuscitation was obtained using a semi-structured questionnaire and audit was with a Proforma following on-site facility visits. Data was analysed using SPSS v20 and displayed in tables and graphs. RESULTS: all health care workers had resuscitated newborns but only 58(57.4%) had ever used a bag and mask, 53(50%) used stethoscopes and 19(17.9%) had resuscitation protocol in their facilities. Fifteen (53.6%) health centres had functional newborn-specific bag and masks, 11(39.3%) had suction machines and 5(25%) had empty oxygen cylinders. CONCLUSION: primary health care workers´ experience of newborn resuscitation is very limited and some primary health centres were grossly unequipped. Neonatal resuscitation training interventions and supplies of neonatal resuscitation equipment are urgently needed.